Impact of Training to Improve Knowledge on Blood Transfusion among Health Care Providers from Tertiary Hospitals in Tanzania (Tanzania Medical Journal, 2020)
Background: Blood transfusion is a lifesaving therapy which is linked to the adverse outcome when given inappropriately. Inadequate knowledge and skills among health care providers have been reported to contribute to safety issues for recipients and wastage of the precious resource. This study was conducted to determine the impact of training of health care providers in Tanzania on improving the knowledge regarding the transfusion of blood and blood components. Methodology: This was a cross-sectional study which used secondary data from pre and post training assessment questionnaire whereby trainees answered the same set of questions before training (pre-test) and after training (post-test). The questionnaire consisted of two Likert scale questions and eight YES/NO questions which assessed the perception of clinicians, nurses and Laboratory personnel on blood transfusion practices. Moreover, there were thirty multiple-choice questions for assessment of basic knowledge related to usage of blood and blood components. Results: One hundred and eleven (111) health care providers who attended training on blood transfusion were recruited into this study, out of which 72.1% (80/111) were from secondary health care facilities and 6.3% (7/111) were from tertiary health care facilities. The pre-test mean percent score was 32.8% (SD ±12.9%), while the post-test mean percent score was 56.6% (SD ±12.9%). The mean percentage of knowledge gain was 26.6% (SD±13.0%) and 27.1% (SD±12.5%) for health care providers and National Blood Transfusion Service staff respectively. It was observed that only 25.8% (24/93) and 19% (19/100) of participants were aware of the transfusion timing of various blood components and principles of platelet transfusion, respectively. Regarding bedside blood handling practices, only 52.9% (46/87) responded, ‘warm whole blood unit and packed red blood by putting under room temperature for 30 minutes and majority of participants 63.1% (65/103) reported not to ask for consent before blood transfusion.Conclusion: There was a modest improvement in the knowledge on blood transfusion practice among participants. Overall performance of participants increased from 33% in pre-test to 57% in post-test. Therefore, this study has shown the positive impact of training for health care providers in improving their knowledge. We recommend regular on job training courses and mentorship program for health care providers for proficiency in clinical transfusion practice.Key words: Blood Transfusion, Training, Health care providers.